1998
DOI: 10.1557/proc-507-517
|View full text |Cite
|
Sign up to set email alerts
|

Performance of μ-Si:H Solar Cells with Amorphous P-Layer

Abstract: We investigated p-i-n solar cells with microcrystalline absorber but amorphous contact layers. Fill factor and open circuit voltage depend sensitively on the p/i interface. Using an optimized design of the p/i interface, cells with fill factors up to 65% and open circuit voltages of 0.45 V were deposited on amorphous p-layers. They are comparable to cells on microcrystalline p-layers. A further increase of the open circuit voltage was achieved by variation of the p/i interface treatment but up to now it was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Such characteristics could only be modeled for i-layers consisting of two distinctly different layersa widegap amorphous layer and a narrow gap microcrystalline one. Such an approach was also successful in simulating the results of earlier studies of intrinsic µc-Si:H growth on p-a-SiC:H [20]. The results of the simulation for cell C is shown as a solid line in Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Such characteristics could only be modeled for i-layers consisting of two distinctly different layersa widegap amorphous layer and a narrow gap microcrystalline one. Such an approach was also successful in simulating the results of earlier studies of intrinsic µc-Si:H growth on p-a-SiC:H [20]. The results of the simulation for cell C is shown as a solid line in Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Surface treatments can also impact the growth and nucleation of the microcrystalline phase. 25,26 For example, Koh et al have investigated the eect of using H 2 plasma pretreatments on a-Si : H i-layers on the nucleation of a subsequent p-layer. 26 They found that with the H 2 plasma pretreatments, they were able to promote immediate nucleation of microcrystalline material.…”
Section: Amorphous Silicon-based Thin-®lmsmentioning
confidence: 99%